Optical signal and optical axes in uniaxial and biaxial nematic phases. (1st February 2019) - Simões, M.; Bertolino, W. H. P.; Davincy, T.; Braga, W. S.; Santos, O. R.; Luders, D. D.; Sampaio, A. R.; Kimura, N. M.; Palangana, A. J.
ABSTRACT: In this work we will study the behavior of the optical signal and optical axes along the continuous transition of a lyotropic system from a nematic discotic (N D ) phase to a nematic calamitic (N C ) phase; we will study in detail the case in which there is a biaxial nematic (N B ) phase at the interstice between these two uniaxial phases. It will be shown that the optical signal and optical axes change simultaneously in order to agree with the optical signals of the uniaxial phases at their borders: the optical signal is positive at the frontiers with theN D phase and it turns to be negative at the frontiers with theN C phase. Concomitantly, the optical axes rotates from thee → z direction to thee → x direction. We will illustrate these findings with experimental data that confirm our results.